Resonance and Damping Ratio Analysis of the Baiturrahman Mosque Tower Based on Earthquake Ground Shaking - simanjuntak, Noviana Sihotang; Umar Muksin; Idris, Yunita; Andi A. Rusdin (UIR PRESS, 2025)
Aceh is a region of tectonic activity, characterized by high seismicity. This inherent seismic hazard endangers the stability of vertical structures, such as mosque towers. The objective of this study is to analyze the dynamic characteristics of the Main Tower of the Baiturrahman Grand Mosque by estimating its natural frequencies and damping ratios. These parameters are used to evaluate the structural vulnerability of the mosque. The study obtained data from multilevel microtremor measurements on each floor of the tower. These measurements were analyzed using two methods. The Horizontal to Vertical Spectral Ratio (HVSR) method identified the dominant frequency in the basement. The Random Decrement Method (RDM) determined the natural frequency and damping ratios at each level of the structure. The results indicate that the natural frequency of the tower ranges from 1.16 to 4.32 Hz, with a damping ratio of 0.91% to 22.97%, which is within the established range for reinforced concrete structures. The substandard value can cause the building to oscillate easily when earthquake shocks occur. The analysis identified the upper floors, specifically 3 and 4, to be the primary sites of resonance, with ratios reaching 11-12%. The significant negative correlation between height and natural frequency indicates that the upper part of the structure is more prone to low-frequency earthquakes. The implications of this study are significant in light of their potential to enhance the understanding of the structural resonance risks and provide a technical basis for planning mosque towers in earthquake-prone areas.